Le traité canado-américain des eaux limitrophes et la Commission mixte internationale - Cohen, Maxwel (Études internationales, 1980)
The general character of Canada-U.S. relations would have been sharply different in the past 65-70 years had there not been established the International Joint Commission under the Boundary Waters Treaty of 1909.That Treaty anticipated in a remarkably prophetic way the lively and sometimes dangerous disputes that arise over shared water resources, boundary and trans-boundary. By providing a mechanism for the settlement of disputes over boundary and trans-boundary water courses, lakes, rivers, etc. and by providing also an investigative mechanism for all other disputes that' may take place along the boundary, the framers of the Boundary Waters Treaty created perhaps better than they knew. For the International Joint Commission has proven to be an instrument of flexibility and high utility. For almost 70 years it has issued Orders of Approval in over 50 cases involving the construction of works affecting the levels and flows of boundary waters as well as causing trans-boundary waters to rise at the boundary and therefore, requiring the approval of the Commission. The whole question of water use/water allocation between neighbouring states sharing common river basins or having rivers and lakes as boundaries is involved in this exercise.It could not have been foreseen, however, that the pioneer language of the pollution provisions of the Boundary Waters Treaty should have moved the Commission with ease into the environmental era. While the Commission was investigating pollution of water questions as early as 1912, and while it recommended a Canada-U.S. Great Lakes Pollution Treaty as early as 1920, it was a great achievement of both countries in signing the Great Lakes Water Quality Agreement in 1972 and again in 1978, which created the massive environmental role as monitor, co-ordinator and advisor that the Commission now plays in relation to both governments in the Great Lakes basin, and also, in the other watersheds along the 5 500 mile frontier of both countries.With the rise in the knowledge of air pollution, and the interfacing between air, water and land use, there is now a whole complex that is ecologically at the basis of the concerns of Canada and the United States and is of prime interest to the Commission, and has become a fundamental aspect of its work.The future of the Commission is vital to the future of both countries as its successful past has been in maintaining reasonably friendly relations despite the tensions which disputes over water resources can cause. It is the thrust of this paper to describe and demonstrate the processes in dispute avoidance and dispute settlement, in shared resource-planning, for which the Boundary Waters Treaty, the Great Lakes Quality Agreement and the work of the Commission now stand.